Influence of Al content and pre-oxidation on the aqueous corrosion resistance of binary Fe-Al alloys in sulphuric acid. (1st April 2019) - Peng, Jian; Moszner, Frank; Rechmann, Julian; Vogel, Dirk; Palm, Martin; Rohwerder, Michael
Highlights: The effect of Al content on the corrosion resistance of Fe-Al alloys was revealed. Passive film structure on Fe-25Al was evaluated by XPS. The oxide layer effectively protected Fe-25Al against corrosion in H2 SO4 . Abstract: The influence of Al content and pre-oxidation on the corrosion behavior of binary Fe-Al alloys in 0.0126 M H2 SO4 was investigated. The minimum Al content for forming a passive film on binary Fe-Al at 25 °C is 15 at.% and passivation improves up to 25 at.% Al. X-ray photoelectron spectroscopy measurements show that the passive film on Fe-25Al is enriched in Al and consists of an outer layer of mixed Al and Fe hydroxides and an inner layer of Al oxide. The oxide layer generated at 1000 °C effectively protected against aqueous corrosion in H2 SO4 .